2020
DOI: 10.1113/ep088061
|View full text |Cite
|
Sign up to set email alerts
|

Low‐dose lithium feeding increases the SERCA2a‐to‐phospholamban ratio, improving SERCA function in murine left ventricles

Abstract: The sarco(endo)plasmic reticulum Ca 2+ -ATPase (SERCA) pump is responsible for regulating calcium (Ca 2+ ) within myocytes, with SERCA2a being the dominant isoform in cardiomyocytes.Its inhibitor, phospholamban (PLN), acts by decreasing the affinity of SERCA for Ca 2+ . Changes in the SERCA2a:PLN ratio can cause Ca 2+ dysregulation often seen in patients with dilated cardiomyopathy and heart failure. The enzyme glycogen synthase kinase-3 (GSK3) is known to downregulate SERCA function by decreasing the SERCA2a:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 40 publications
1
22
0
Order By: Relevance
“…11,[47][48][49] Thus, finding ways to reduce the amount of PLN relative to SERCA is an active field of research. 50,51 Long considered to be the functional homolog of PLN, sarcolipin (SLN) is a small 31 amino acid protein that binds to and regulates the SERCA pump. 52,53 Like PLN, SLN can reduce SERCA's affinity for Ca 2+ .…”
Section: Serca Uncoupling: a Role For Nnat?mentioning
confidence: 99%
See 3 more Smart Citations
“…11,[47][48][49] Thus, finding ways to reduce the amount of PLN relative to SERCA is an active field of research. 50,51 Long considered to be the functional homolog of PLN, sarcolipin (SLN) is a small 31 amino acid protein that binds to and regulates the SERCA pump. 52,53 Like PLN, SLN can reduce SERCA's affinity for Ca 2+ .…”
Section: Serca Uncoupling: a Role For Nnat?mentioning
confidence: 99%
“…Western blotting and co-immunoprecipitation protocols were performed as previously described using 4%-15% TGX precast gels (Bio-Rad Laboratories) and PVDF membranes. 50,[60][61][62] Primary antibodies for NNAT were obtained from ProteinTech (26905-1-AP), whereas SERCA1a (MA3-912) and SERCA2a (MA3-919) were obtained from ThermoFisher…”
Section: F I G U R Ementioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Wang X et al demonstrated that lithium induces upregulation of ITCH and promotes ubiquitylation and degradation of Gli1, a regulator of the Hedgehog signaling pathway, in PANC-1 cells [ 229 ]. A recent report demonstrated that low-dose lithium feeding increases sarcoplasmic/endoplasmic reticulum Ca 2+ ATPase 2a (SERCA2a) to phospholamban ratio and improved SERCA function in the murine left ventricle [ 230 ], suggesting a protective role in the heart. Although the precise mechanism by which lithium upregulates ITCH is unclear, there is a possibility that ITCH target therapy is beneficial in the heart.…”
Section: Drug Discoverymentioning
confidence: 99%